Proceedings of the Second International Conference on Performance-Based and Life-Cycle Structural Engineering (PLSE 2015) 2015
DOI: 10.14264/uql.2016.1117
|View full text |Cite
|
Sign up to set email alerts
|

CFRP strengthened CFST columns under vehicular impact

Abstract: Concrete filled steel tubular (CFST) columns are increasingly used in bridge piers and high-rise buildings due to their excellent axial load bearing capacity. These columns may experience severe damage or failure due to transverse impact of vehicle collisions. In this study, numerical investigation is carried out to evaluate the effect of carbon fibre reinforced polymer (CFRP) strengthening CFST columns under vehicular impact. The CFRP composites damage mechanisms are simulated to account four different failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Alam et al, [13] indicated that strengthening concrete by (CFRP) sheets improved its impact resistance. Wherefore this study suggested utilizing this technique to avoid collapse of (CFST) column subjected to vehicular impact in bridges.…”
Section: Use Of Carbon Fiber Reinforced Polymer (Cfrp) Jacketsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alam et al, [13] indicated that strengthening concrete by (CFRP) sheets improved its impact resistance. Wherefore this study suggested utilizing this technique to avoid collapse of (CFST) column subjected to vehicular impact in bridges.…”
Section: Use Of Carbon Fiber Reinforced Polymer (Cfrp) Jacketsmentioning
confidence: 99%
“…They also explained that (RACFST) specimens had better deformationresistance capability as normal (CFST) specimens. Alam et al, [13] performed Finite element investigation on Carbon Fiber Reinforced Polymer (CFRP) strengthening (CFST) column under transverse impact loading. They indicated that strengthening concrete by (CFRP) sheets improved its impact resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Alam et al [120] studied CFRP strengthened CFST columns under vehicular impact. Nevertheless, Aslani et al [121] predicted the axial load capacity of high-strength concrete filled steel tubular columns. Additionally, Ganesh Prabhu et al [122] investigated the compressive behavior of circular CFST columns externally reinforced using CFRP composites.…”
mentioning
confidence: 99%